Synthesis and Characterization of Silsesquioxane-Based Polymer Hybrids with Controlled Structure - Ricardo O.R. Costa; Wander L. Vasconcelos; Richard M. Laine (Materials Research, 2002)
We have developed a method to obtain polymer hybrids with control of inorganic content and molecular configuration. Hybrid poly(methyl methacrylate) (PMMA) was obtained via atom transfer radical polymerization (ATRP) initiated by octafunctional cubic silsesquioxanes using CuCl as catalyst. Two different ATRP initiators obtained by attaching specific chemical groups to the cubic silsesquioxane were employed to produce two types of hybrids with different architectures. While a-bromide ester groups generated a star-shaped polymer, the benzyl chloride groups produced longer and more linear polymeric chains containing the cubic silsesquioxane. These results were explained on the basis of the low initiation efficiency of benzyl chloride groups for PMMA, leading to polymers with molecular weights (Mn) and polydispersities (PDI) higher than the expected ones.